Simvastatin inhibits leptin-induced hypertrophy in cultured neonatal rat cardiomyocytes - Hu Tai-ping; Xu Fang-ping; Li Yuan-jian; Luo Jian-dong (Acta Pharmacologica Sinica, 2016)
Aim: To test the hypothesis that statins inhibit leptin-induced hypertrophy in cultured neonatal rat cardiomyocytes. Methods: Cultured neonatal rat cardiomyocytes were used to evaluate the effects of simvastatin on leptin-induced hypertrophy. Intracellular reactive oxygen species (ROS) levels were determined by using 2', 7'-dichlorofluorescein diacetate (DCF-DA) fluorescence. Total intracellular RNA and cell protein content, which serve as cell proliferative markers, were assayed by using propidium iodide (PI) fluorescence and the Bio-Rad DC protein assay, respectively. The cell surface area, an indicator of cell hypertrophy, was quantified by using Leica image analysis software. Results: After 72 h treatment, leptin markedly increased RNA levels, cell surface area, and total cell protein levels in cardiomyocytes, which were significantly inhibited by simvastatin or catalase treatment. ROS levels were significantly elevated in cardiomyocytes treated with leptin for 4 h compared with those cells without leptin treatment. The increase in ROS levels in cardiomyocytes induced by leptin was reversed by treatment with simvastatin and catalase. Conclusion: Simvastatin inhibits leptin-induced ROS-mediated hypertrophy in cultured neonatal rat cardiac myocytes. Statin therapy may provide an effective means of improving cardiac dysfunction in obese humans.